Video Game Microtransaction Ethics - Steedley, Evan A.; Corbitt, Michael D.; Shipman, Erik J. (My University, 2020)
In this paper we define the terms video game, microtransaction, and loot-box, among others. We differentiate the types of microtransactions, such as what kind of transactions affect the progression of the game. We also comment on the history of how microtransactions have been used and the public’s reaction to their use, how current laws could affect microtransactions, and attempts to introduce laws and regulations for video games. This paper covers whether or not all, some, or none of the current uses of microtransactions are legal and/or ethical using our own deductions along with a short survey we have distributed among the Valdosta State University students. We concluded that there are no laws specifically applying to microtransactions or loot-boxes in gaming in the United States, and that video game players currently do not mind microtransactions as long as they do not feel pressured or give another player an unfair advantage.